SOCIAL FUNCTIONING OUTCOME MEASURES IN SCHIZOPHRENIA WITH A FOCUS ON SUITABILITY FOR INTERVENTION RESEARCH : A SYSTEMATIC REVIEW - Ria Novitasari, Devi (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: The field and social functioning measurement have altered. Cognitive deficits and unpleasant symptoms predict social functioning, driving the creation and evaluation of remedies. Research shows that these traits may affect social functioning differently across domains. Multiple reviews have explored social functioning measurement. The most complete showed that many schizophrenia measures were unvalidated, interventional research reliability and validity standards were unknown, and many were too demanding for research and clinical practice. The aim: This article showed social functioning outcome measures in schizophrenia with a focus on suitability for intervention research. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 125 articles, whereas the results of our search on SagePub brought up 113 articles. The results of the search conducted for the last year of 2013 yielded a total 67 articles for PubMed and 42 articles for SagePub. In the end, we compiled a total of 24 papers, 16 of which came from PubMed and 8 of which came from SagePub. We included seven research that met the criteria. Conclusion: Numerous social functioning assessments have been validated in schizophrenic populations, but evidence on their strengths and weaknesses is scarce. We described practical aspects, content and coverage, quality, and frequency of application of regularly used measurements.